2009
DOI: 10.1063/1.3148865
|View full text |Cite
|
Sign up to set email alerts
|

Surface anisotropy, hysteretic, and magnetic properties of magnetite nanoparticles: A simulation study

Abstract: In this study we address the role of surface anisotropy on the hysteretic properties of magnetite Fe3O4 nanoparticles and the circumstances yielding both horizontal and vertical shifts in the hysteresis loops. Our analysis involves temperature dependence and particle size effects. Different particle sizes ranging from 2 up to 7 nm were considered. Our theoretical framework is based on a three-dimensional classical Heisenberg model with nearest magnetic neighbor interactions involving tetrahedral (A) and octahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 66 publications
6
30
0
1
Order By: Relevance
“…In the case of spherical Fe 3 O 4 MNPs, a Monte Carlo simulation study found an EB effect for particle sizes less than 2.5 nm, where the surface anisotropy ( K S ) resulting from disordered surface spins is assumed to be large compared to the core cubic magnetocrystalline anisotropy ( K C ) [61]. More information on Monte Carlo simulations can be found at the end of the article, in Appendix A.…”
Section: Exchange Bias Effect In Single-component Solid Nanoparticlesmentioning
confidence: 99%
“…In the case of spherical Fe 3 O 4 MNPs, a Monte Carlo simulation study found an EB effect for particle sizes less than 2.5 nm, where the surface anisotropy ( K S ) resulting from disordered surface spins is assumed to be large compared to the core cubic magnetocrystalline anisotropy ( K C ) [61]. More information on Monte Carlo simulations can be found at the end of the article, in Appendix A.…”
Section: Exchange Bias Effect In Single-component Solid Nanoparticlesmentioning
confidence: 99%
“…The concept of a chemically uniform, but magnetically distinct, core and canted shell is not without precedent [14,24], though not previously reported experimentally. We speculate that the lack of radial symmetry arises primarily from the competition between interparticle coupling within the nanoparticle array [21] (that sets a net direction) and nanoparticle surface anisotropy [12,13] (that promotes outward spin canting). For example, experiment [3] has shown that intraparticle exchange biasing can be altered by varying nanoparticle packing distance.…”
Section: Fig 1 (Color Onlinementioning
confidence: 99%
“…Similarly, we cannot quantify boundary fuzziness or degree of overlap between core and shell, but we can conclude from the M 2 PERP scattering that magnetic shells of nearly uniform magnitude and direction exist. Thus, models involving a disordered outermost shell [6][7][8][9], a canted moment that extends throughout the entire volume of the particle, and ''hedgehoglike'' [12] or ''throttle'' [13] symmetry do not fit M 2 PERP and are excluded. The isolation of M 2 PERP demonstrated here is only possible using diffraction or other spatially sensitive techniques since moments quickly average to zero across the sample, as evidenced by an equivalence of M 2 Y and M 2 Z [22].…”
Section: Fig 1 (Color Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…As the particle size is reduced, the density of magnetic bonds decreases as long as the proportion of undercoordinated ions on the surface becomes grater. Therefore, smaller fields enable more easily the reversal of spins and lead to lower switching fields for smaller sizes [42].…”
Section: Resultsmentioning
confidence: 99%